An An Analysis of Code-Switching as Used on @aliciaserena’s TikTok Account - Atika, Melania Desmita; Teda Ena, Ouda (e-Journal of Linguistics; Vol 18 No 2 (2024): ejl-JulyDO - 10.24843/e-jl.2024.v18.i02.p12, 2024)
Code-switching is a sociolinguistic phenomenon defined as the combination of two or more varieties, or codes used in the same utterance (Wardhaugh, 2006). This research focuses on analyzing the types of code-switching using Wardhaugh’s theory (2006) and analyzing the function of code-switching using Gumperz’s theory (1982). The research investigates TikTok videos from the account, in which the focus of the content is on education, especially English learning. The method used in this study is the descriptive qualitative method. The researchers employed the observation method using the checklist. The results of the study show that 2 types of code-switching and only 5 of 6 functions of code-switching were found.